درجة تواجد الأزمات التربوية في ظل الأزمة الحالية "بحث ميداني في مدارس الحلقة الأولى من التعليم الأساسي في محافظة اللاذقية" - علي نايفة; غانم ثناء; ناصر رشا (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يهدف البحث للتعرف إلى درجة تواجد الأزمات التربوية في ظل الأزمة الحالية في مدارس الحلقة الأولى من التعليم الأساسي في محافظة اللاذقية، وكذلك إلى الفروق في تقدير أفراد عينة البحث لدرجة تواجد الأزمات التربوية في مدارس الحلقة الأولى من التعليم الأساسي تبعاً للمتغيرات الآتية (الجنس، ومكان المدرسة، والمؤهل العلمي والتربوي، وعدد سنوات الخبرة، والمسمى الوظيفي)، واعتمد البحث على المنهج الوصفي، كما استخدم استبانة مؤلفة من (54) عبارة كأداة لجمع المعلومات من عينة البحث التي بلغت (299) فرداً من الإداريين والمعلمين في مدارس الحلقة الأولى من التعليم الأساسي في محافظة اللاذقية للعام الدراسي (2013- 2014)، وأظهرت النتائج أن درجة تواجد الأزمات التربوية كانت متوسطة، وأظهرت أيضاً أنه لا توجد فروق بين تقديرات أفراد عينة البحث بالنسبة لدرجة تواجد الأزمات في مدارس الحلقة الأولى من التعليم الأساسي تبعاً للمتغيرات التالية (الجنس_ والمؤهل العلمي والتربوي_ وعدد سنوات الخبرة)، وهناك فروق بين تقديرات أفراد عينة البحث بالنسبة لدرجة تواجد الأزمات في مدارس الحلقة الأولى من التعليم الأساسي تبعاً لمتغير مكان المدرسة لصالح المدينة، ولمتغير المسمى الوظيفي بين (الموجهين التربويين وكل من المرشدين الاجتماعيين والمعلمين) لصالح الموجهين التربويين، وبين (المعلمين وكل من المديرين ونوابهم) لصالح المديرين ونوابهم. This research aims to identify the level of existence of educational crisis during the current crisis at the first cycle schools of the basic learning In Lattakia, it aims also to identify the differences in their views about the existence of crisis at the first cycle schools of the basic learning according to (gender, school location, scientific and educational qualification, years of experience, job title). This research adopts the descriptive approach, and it uses a questionnaire that consists of (54) phrases as a tool to collect data from the sample of the research which consists of (299) administrators and teachers in the first cycle schools of the basic learning in Lattakia (2013- 2014). Results have shown that the crisis was present to an intermediate level. As indicated by results there are no differences among sample members point of view regarding the level of crisis in the first cycle schools of the basic learning according to (gender, scientific and educational qualification, years of experience). Whereas there are differences according to school location in favor of the city, and job title among (teachers, social counselor, educational directors) in favor of educational directors also among (teachers, principals, vice principals) in favor principals and vice principals.